Micropipette replacement for automated cell micromanipulation - Wijaya, Nico Fendy (2018)
Pre-implantation Genetic Diagnosis (PGD) is a procedure that combine in vitro fertilization (IVF) and genetic analysis to decrease the risk of genetic disease pass down from their parents [9]. PGD is known for a complex and highly skilled procedure which highly dependent on the operator. Therefore, there is an attempt to automate PGD procedure to give better efficiency and higher success rate. One of the step in PGD is to change the micropipette in every cycle to avoid cross contamination among different zygote. The objective of this project is to introduce a mechanism to change the pipette and study the advantages and disadvantages of different mechanism that will make up the full automated PGD machine. This report comprises of 3 different design ideas of the pipette storage, pipette holder, and the motion that the manipulator must undergo to complete the task. Each idea will be discussed in detail about their advantages and disadvantages. After going through several design iterations and compare the other concept, it was decided that the best design (concept C) is a specially design chain-like storage equipped with c-clip that is used to store pipette, this design is preferred for their large capacity and simplified the motion needed to retrieve and store the micropipette. Pipette holder have D-shape profile to ensure pipette orientation and a clip to hold them together. This concept is superior because of the fact that the motion is done by the manipulator itself with only 2-DoF. Calculation on the mass, volume, and inertia is also discussed in the report.